Antiprotozoal Germacranolide Sesquiterpene Lactones from Tanacetum sonbolii - Mofidi Tabatabaei, Sahar; Nejad Ebrahimi, Samad; Salehi, Peyman; Sonboli, Ali; Tabefam, Marzieh; Kaiser, Marcel; Hamburger, Matthias; Moridi Farimani, Mahdi (Planta Medica, 2019)
A phytochemical investigation of extracts from flowers and aerial parts of Tanacetum sonbolii afforded 7 new germacranolide sesquiterpene lactones. The structures were established by a combination of 1- and 2-dimensional nuclear magnetic resonance spectroscopy, high-resolution mass spectrometry, and electronic circular dichroism. The in vitro antiprotozoal activity of the compounds against Trypanosoma brucei rhodesiense and cytotoxicity against rat myoblast (L6) cells were determined. Compounds 4 and 5 showed IC50 values of 5.1 and 10.2 µM and selectivity indices of 3.9 and 4.0, respectively.
Keywords: Tanacetum sonbolii; Asteraceae; sesquiterpene lactone; electronic circular dichroism; antiprotozoal activity; Trypanosoma brucei rhodesiense